The influence of family and social problems on treatment outcomes of persons with co-occurring substance use disorders and PTSD. (3rd May 2016) - Saunders, Elizabeth C.; McLeman, Bethany M.; McGovern, Mark P.; Xie, Haiyi; Lambert-Harris, Chantal; Meier, Andrea
Abstract: Objective : Family and social problems may contribute to negative recovery outcomes in patients with co-occurring substance use and psychiatric disorders, yet few studies have empirically examined this relationship. This study investigates the impact of family and social problems on treatment outcomes among patients with co-occurring substance use and posttraumatic stress disorder (PTSD). Method : A secondary analysis was conducted using data collected from a randomized controlled trial of an integrated therapy for patients with co-occurring substance use and PTSD. Substance use, psychiatric symptoms and social problems were assessed. Longitudinal outcomes were analyzed using generalized estimating equations (GEEs) and multiple linear regression. Results : At baseline, increased family and social problems were associated with more severe substance use and psychiatric symptoms. Over time, all participants had comparable decreases in substance use and psychiatric problem severity. However, changes in family and social problem severity were predictive of PTSD symptom severity, alcohol use and psychiatric severity at follow-up. Conclusions : For patients with co-occurring substance use and PTSD, family and social problem severity is associated with substance use and psychiatric problem severity at baseline and over time. Targeted treatment for social and family problems may be optimal.